2019
DOI: 10.1051/jnwpu/20193720401
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Properties of V-Shaped Surface Texture under Oil Lubrication Condition

Abstract: In order to study the tribological properties of V-shaped texture under oil lubrication conditions, the loading force and speed are selected as the influencing factors, each factor selected six levels. Experimental study on friction and wear of V-shaped texture with ring arrangement is finished by MMG-10 Multifunctional Friction and Wear Testing Machine, and the data of the experimental results are analyzed by using Matlab. The results show that there is a near linear relationship between the friction coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Because the texture shape has a great influence on the tribological properties of the texture, many researchers are committed to improving the tribological properties of the surface texture by improving the texture shape. Wu et al 101 carried out tribological tests and simulation analysis on the surface of V-shaped texture under oil lubrication. It was found that the friction coefficient decreased with the increase of load and speed, and basically showed a linear relationship, and the load had a great influence.…”
Section: Texture Shapementioning
confidence: 99%
“…Because the texture shape has a great influence on the tribological properties of the texture, many researchers are committed to improving the tribological properties of the surface texture by improving the texture shape. Wu et al 101 carried out tribological tests and simulation analysis on the surface of V-shaped texture under oil lubrication. It was found that the friction coefficient decreased with the increase of load and speed, and basically showed a linear relationship, and the load had a great influence.…”
Section: Texture Shapementioning
confidence: 99%
“…The results showed that the friction coefficient on the carbide surface was minimized at a microtexture density of 9.5%. Via certain studies, it was concluded that V-shaped microtextures with a single orientation have better wear reduction effects than the traditional circular, square and grooved microtextures due to their unique convergent wedge (Hamilton et al , 1967; Wu et al , 2019). Despite the clear advantages of V-shaped microtextures, there remains a noticeable lack of systematic and comprehensive research on the underlying antiwear theory, friction and wear performance and the mechanisms involved (Marian et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that textured surfaces with non-smooth morphology exhibit excellent performance in noise reduction and wear resistance [9,10]. To optimize the texture structure, numerous experimental studies have been carried out on textured surfaces with varying parameters, such as texture shape and size [11,12]. Zhang et al investigated the frictional wear of grooved textures under sand-containing oil lubrication conditions.…”
Section: Introductionmentioning
confidence: 99%